Analysis of Decision No 61/Pid.Sus Anak/2021/Pn Mdn On the Case of a Child as A Violator of The Crime of Abuse - Rodiatun Adawiyah; O.K. Isnainul; Muhammad Arif Prasetyo; Jane febrision br. Manurung; Edward Halim; Tamarsa Adea Putri Br Sitepu (Warmadewa Press, 2024)
Children are the next generation of the nation and have important responsibilities in the survival of the nation and state. For every child to be able to assume his responsibility as the heir of the nation, he must be given the widest possible opportunity to grow and develop optimally, both physically, spiritually, and socially. The purpose of this study is to determine the application of Law No. 35 of 2014 concerning amendments to Law No. 23 of 2002 concerning Child Protection in Decision No. 61/PID.SUS ANAK/2021/PN MDN. This research uses normative research methods. The result of this study is that according to the provisions of the Child Protection Law, children must be protected both as perpetrators of criminal acts, victims of criminal acts, and witnesses to criminal acts. In general, the purpose of the legal protection of children is to maintain the rights and obligations of children so that they can grow and develop naturally both physically, mentally, spiritually, and socially